Repositioning Aswaja Sufism: A Normative-Critical Analysis of adicalism, Materialism, and Secularism in Modern Society - Ahmad; Muhammad Zaqi Ramadhan; Kahlilurrahman Kahlilurrahman; M. Anshari (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2026)
Purpose of the study: This study aims to critically reconstruct Aswaja Sufism as a normative-ethical response to three contemporary challenges radicalism, materialism, and secularism within modern society. Methodology: This study employed a qualitative normative-philosophical approach using library research, contextual hermeneutic interpretation, thematic coding, and comparative synthesis. Primary sources included classical Sufi texts, particularly works of Al-Ghazali and Al-Qushayri, supported by contemporary social theory literature. Data were analyzed through conceptual reconstruction without statistical software. (56 words) Main Findings: The study finds that tawassuth functions as ethical reflexivity against absolutism, zuhd operates as moral regulation within consumer capitalism, and ihsan strengthens inward accountability in plural public life. These principles collectively serve as complementary normative resources that reinforce moral integrity without replacing structural political or economic reforms in modern society. Novelty/Originality of this study: This study advances existing scholarship by systematically reconstructing Aswaja Sufism beyond devotional-historical analysis into a normative-critical framework integrated with modern social theory. It introduces an ethical reconstruction matrix translating classical Sufi principles into contemporary educational, civic, and institutional applications, thereby bridging spiritual moral psychology with structural modern challenges.